Fossil ants of the genus Gesomyrmex Mayr (Hymenoptera, Formicidae) from the Eocene of Europe and remarks on the evolution of arboreal ant communities - Dlussky, Gennady M.; Wappler, Torsten; Wedmann, Sonja (Zootaxa, 2009)
The formicid genus Gesomyrmex is reviewed and several new species are described from the middle Eocene (about 47 Ma) of Grube Messel, Germany, and from the middle Eocene (about 43 Ma) of Eckfeld maar, Germany. The new taxa are Gesomyrmex curiosus n. sp., Gesomyrmex breviceps n. sp., and Gesomyrmex pulcher n. sp. from Messel, and Gesomyrmex flavescens n. sp., and Gesomyrmex germanicus n. sp. from Eckfeld maar. Two previosly described Oligocene species must be excluded from Gesomyrmex. Former G. expectans Théobald, 1937 is transferred to Eoformica expectans (Théobald, 1937) (comb. nov.), and former G. miegi Théobald, 1937 has to be considered as Formicidae incertae sedis (comb. nov.). A key to the living and fossil reproductive female caste (gyne) of the genus Gesomyrmex is provided. Given the fossil records of Gesomyrmex hoernesi Mayr, 1868 from different European amber deposits the presence of this genus in Europe during the Eocene is well established. Both extant and fossil Gesomyrmex species have an arboreal mode of life. The comparison of arboreal ant faunas from Eocene to Recent times shows that their community structure apparently changed considerably during this period. We infer that Gesomyrmex, along with other genera, was most prosperous during the middle Eocene of Europe, and today has a relict distribution in southern Asia.